Amenities and location of hotels: a micro-economic model and estimations. - Stephanie Truchet; Jean-Marc Callois; Francis Aubert; Virginie Piguet (European Regional Science Association (ERSA), 2010)
Among different determinants, amenities play a major role in the location of tourism activities. In Tourism Economics, an extensive literature investigates the influence of amenities either on destination choice made by tourists or on economic development, generally at a regional or national level. This paper aims at analysing the influence of amenities on the location of hotels at local level. In a first part, after a presentation of the context of our work and a brief survey of existing literature on the link between amenities and tourism, we introduce and describe the different amenities features that will be analysed. In a second part, using a micro-economic model of hotel entry inspired by urban economics literature, we analyse the influence of amenities characteristics on a tourist bid-rent function and then on the number of hotels entering the market. The third part will be dedicated to an estimation of the effect of amenities on the creation of new hotels at the French 'Bassins de vie' level, which are functional economic areas.
Keywords: 330